Controllable Coordination Self‐Assembly Based on Flexible Tripodal Ligands: From Finite Metallocages to Infinite Polycatenanes Step by Step. Issue 4 (6th July 2015) - Chen, Qihui; Chen, Lian; Jiang, Feilong; Hong, Maochun
Abstract This article describes the developments in coordination self‐assembly based on flexible tripodal ligands with different metal species. Various finite metallocages such as M3L2, M6L8, M6L4, M4L4 and different catenanes based on discrete metallocages constructed from flexible tripodal ligands with suitable metal species are presented here. Many M3L2 metallocages based on ligands L1–L12 and different two‐coordinated metal species have been prepared, in which various Ag(I) salts and other metal species that have been protected by suitable groups, such as Zn(OAc)2, ZnBr2, and PdBr2, have been used as effective acceptors. All of the M6L8‐type metallocages are constructed from ligands L2 or L12–L20 and different four‐coordinated metal species, such as various palladium(II) salts or NiCl2, and have similar topological structures. Only a few discrete M6L4‐type metallocages, based on ligands L21–L24, have been reported, using different strategies such as protecting groups and steric hindrance. All of the M4L4‐type cages have similar topological structures and are constructed from ligands L25–L29 with multiple donor sites. More intriguing interlocking ensembles constructed from discrete metallocages are also described here in detail, namely, three [2]catenanes based on ligands L30–L32 and four polycatenanes based on ligands L33–L34.